Pelatihan Dasar Robotika Berbasis STEM bagi Siswa Sekolah Dasar Al-Islah Surabaya - Andika, Yudi; Ardiana, Mirza; Rahma Annisa, Aulia; Sasmita Aji Pambudi, Dwi; Kurnia Mayangsari, Mustika; Muhammad Irsyad, Sholahuddin (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance elementary school students’ understanding and basic skills in STEM-based robotics (Science, Technology, Engineering, and Mathematics) at SD Al-Islah Surabaya, thereby fostering adaptive, creative, and innovative character development in response to the challenges of globalization. The program implementation included the preparation of instructional modules, delivery of theoretical materials, basic programming activities, equipment demonstrations, hands-on practice, and evaluation using observation sheets to assess participant performance. The activity was conducted at SD Al-Islah Surabaya and involved 94 third- and fourth-grade students accompanied by their homeroom teachers. The results indicate that 50% of the students were able to operate the robots they assembled. In addition, students demonstrated high levels of enthusiasm throughout the activities, actively asked questions, and were able to independently attempt and operate simple robotic systems. Overall, the program effectively improved students’ problem-solving skills and critical thinking abilities, while also developing their foundational understanding of STEM concepts and robotics techniques. This initiative is expected to serve as an initial step toward integrating robotics education into the curriculum of the partner school.